3D Nanostructured Polypyrrole/Sodium Alginate Conducting Hydrogel from self-assembly with High Supercapacitor Performance. Issue 8 (3rd August 2017) - Huang, Huabo; Yao, Junlong; Liu, Yulan; Tuo, Xin; Da, Yumin; Zeng, Xiaoping; Li, Liang
ABSTRACT: Due to their possible ideal three dimensional (3D) nanostructures and excellent electrochemical properties, conducting hydrogels have attracted much attention in recent years. Herein, pyrrole monomer was directly dissolved in an aqueous solution of sodium alginate (SA), and was allowed to undergo in-situ polymerization to form polypyrrole (Ppy), resulting in formation of Ppy/SA, a conducting hydrogel, via self-assembly between the polymers. Observation by SEM indicated that the microstructure of the Ppy/SA hydrogel was a typical 3D nano-cylinder network, with the cylinders formed by entanglements of the Ppy and SA molecular chains (cylinder diameter was ∼100 nm). The electrochemical measurements of cyclic voltammetry, galvanostatic charge/discharge and electrochemical impedance spectroscopy indicated that the Ppy/SA hydrogel possessed typical pseudocapacitance, good charging and discharging rate performance, and favorable capacitive behavior; the specific capacity reached up to 249 F/g at the current density of 0.2 A/g. We suggest it has great potential in the field of high-performance electrode materials for supercapacitors.